2019
DOI: 10.1016/j.jnn.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral intravenous catheter practices in Australian and New Zealand neonatal units: A cross-sectional survey

Abstract: A B S T R A C TPeripheral intravenous catheters (PIVCs) are important tools for the provision of treatment for unwell and premature neonates. This study aimed to explore current PIVC practices (i.e. insertion, product selection, complications and management priorities) within Australian and New Zealand neonatal units, to identify areas for innovation and practice change. The survey was distributed via Australian and New Zealand neonatal nursing associations, with 180 respondents (54% Australia; 46% New Zealand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…The very nature of fragile premature skin adversely places the neonate at risk for any skin injury despite etiology. 41 Previous studies have suggested that prematurity and lower BW were associated with injury, but our results found that injuries could also occur in neonates slightly older (30.75 ± 4.6 weeks GA at birth) and heavier (1325.9 ± 944.1 g BW). 11 Therefore, the results of this study demonstrate that neonates of all ages including preterm, late preterm, long-term, and neonates requiring high acuity are at risk for injury.…”
Section: Discussioncontrasting
confidence: 66%
“…The very nature of fragile premature skin adversely places the neonate at risk for any skin injury despite etiology. 41 Previous studies have suggested that prematurity and lower BW were associated with injury, but our results found that injuries could also occur in neonates slightly older (30.75 ± 4.6 weeks GA at birth) and heavier (1325.9 ± 944.1 g BW). 11 Therefore, the results of this study demonstrate that neonates of all ages including preterm, late preterm, long-term, and neonates requiring high acuity are at risk for injury.…”
Section: Discussioncontrasting
confidence: 66%
“… 14 In contrast, a study on neonates in New Zealand stated that the discipline of the inserter might not be the factor causing the peripheral intravenous complication. 21 It is necessary to consider the clinical experience of the nurses in resolving the peripheral infusion cases in LBW.…”
Section: Discussionmentioning
confidence: 99%
“…Nationally, Difficult Intravenous Access (DIVA) affects 30-50% of hospitalised patients [6,7]. Patients at highest risk of DIVA typically fall within the age extremes [8,9], have chronic disease (resultant poor vein quality) [8,10], invisible and/or non-palpable due to excess adipose tissue [2,11]; or live in rural/remote areas, with limited access to advanced practitioners [12]. The consequences of DIVA are significant, with PIVC insertion failure associated with substantial treatment delays [6], increased healthcare costs [13] and significant pain and patient suffering [14,15].…”
Section: Introductionmentioning
confidence: 99%